School Burnout Inventory: Factorial Validity, Reliability, and Measurement Invariance in a Chilean Sample of High School Students - Carmona-Halty, Marcos; Mena-Chamorro, Patricio; Sepúlveda-Páez, Geraldy; Ferrer-Urbina, Rodrigo (Frontiers in Psychology, 2022)
This brief report assessed the psychometric validity and gender invariance of the School Burnout Inventory (SBI) –a measure of students´ exhaustion, cynicism, and inadequacy– in a convenience sample of 972 high school Chilean students ranging between 12 and 18 years old. The results showed that: 1) the SBI produces adequate scores in terms of reliability; 2) a three related factor solution adequately fit to our sample and was invariant across gender; and 3) the SBI scores were significantly related with others related constructs (study-related emotions, psychological capital, and engagement). Overall, the SBI was found to be a reliable and valid inventory to assess school burnout in Chilean high school students.